Thermal barrier / environmental barrier coating anti-CMAS corrosion protection layer and in-situ reaction preparation method thereof
A bionic structure protective layer with vertically grown needle-shaped apatite and a dense bottom layer effectively addresses CMAS corrosion in thermal and environmental barrier coatings, improving adhesion and infiltration resistance, ensuring durability and safety in high-temperature environments.
Patent Information
- Application Number
- CN202311162814.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-09-11
AI Technical Summary
CMAS corrosion poses a significant challenge to thermal and environmental barrier coatings in aircraft engines and gas turbines, leading to premature failure and safety risks due to adhesion and penetration of molten CMAS, which current methods struggle to effectively prevent.
A bionic structure protective layer is formed on the surface of the coatings through an in-situ chemical reaction, comprising a top layer of vertically grown needle-shaped apatite and a bottom layer of a continuous dense layer, achieved by pre-coating CMS amorphous powder on (Gd1-xYbx)PO4 and heat treatment, enhancing CMAS repellency and infiltration resistance.
The bionic structure significantly increases the contact angle of molten CMAS, preventing adhesion and infiltration, maintaining structural integrity under high temperatures, and ensuring compatibility with existing coatings, thus enhancing the durability and safety of the coatings.
Smart Images

Figure CN117165896B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high temperature protective coatings, and specifically relates to a method for improving the corrosion resistance of thermal barrier / environmental barrier coatings against environmental deposits (CMAS), that is, constructing a CMAS corrosion resistant protective layer with a bionic structure on the surface of the coating through an in-situ chemical reaction. In particular, a thermal barrier / environmental barrier coating anti-CMAS corrosion protective layer and an in-situ reaction preparation method thereof are proposed. Background Art
[0002] In order to improve the efficiency and fuel utilization of aircraft engines and gas turbines, their turbine inlet temperatures are constantly increasing. Thermal barrier coating (TBC) is an important thermal protection technology for hot end components of aircraft engines and gas turbines (such as turbine blades); as the turbine inlet temperature further increases, the use temperature of high-temperature alloys will reach its limit, and the use of ceramic matrix composites (CMC) to replace high-temperature alloys will be the general trend. However, CMC is susceptible to water and oxygen corrosion at high temperatures and requires environmental barrier coating (EBC) to provide protection. Therefore, TBC and EBC are key core technologies for hot end components of aircraft engines and gas turbines. Once spalling failure occurs, it will have catastrophic consequences for aircraft engines and gas turbines.
[0003] When aircraft engines and gas turbines are working, especially in desert environments and sandstorm weather, the air they ingest contains a lot of dust, particles, gravel, etc., which enter the combustion chamber, melt at high temperatures, collide with high-speed airflow and adhere to the surface of the hot end components TBC or EBC, severely corroding the coating and causing it to peel off and fail prematurely. These attachments are called environmental deposits, and their main components are CaO, MgO, A1 2 O 3、 SiO 2 , referred to as CMAS. CMAS corrosion has become an important factor that limits the use of TBC and EBC and threatens the safe operation of aircraft engines / gas turbines. It is a difficult problem that needs to be solved urgently; CMAS protection is currently a research hotspot and difficulty in the field of TBC and EBC.
[0004] In order to achieve CMAS corrosion protection for TBC and EBC, on the one hand, it is necessary to minimize the adhesion of molten CMAS on the coating surface, and on the other hand, when molten CMAS inevitably adheres to the coating surface, it is necessary to reduce the melt penetration and damage to the entire coating as much as possible. Inspired by the fact that lotus leaves grow out of mud without getting stained, researchers use laser and other methods to modify the surface of TBC and EBC, construct a lotus leaf-like micro-nano surface structure, and greatly reduce the wettability of molten CMAS on the coating surface. However, the micro-nano structure on the coating surface is easily sintered and degraded at high temperatures, causing the coating to lose its ability to repel molten CMAS. In addition, for coating samples with complex surfaces, it is difficult to use laser methods to accurately construct bionic micro-nano structures. For the most widely used Y 2 O 3 Partially stabilized ZrO 2 When molten CMAS adheres to the surface of (YSZ)TBC, CMAS will quickly react chemically with it, causing the coating to become unstable and structurally damaged. In addition, the CMAS melt will continue to penetrate into the coating, causing serious damage to the entire coating. In order to inhibit the penetration of molten CMAS, the researchers prepared Gd 2 Zr 2 O 7 、Al 2 O 3 、Ti 2 Coatings such as AlC can react quickly with molten CMAS to form a continuous and dense inert crystalline layer on the surface, thereby delaying the continuous infiltration of molten CMAS and improving the coating's resistance to CMAS. However, the above-mentioned inert crystalline layer will significantly thicken during the continuous reaction with molten CMAS, with poor structural stability and no molten CMAS-repellent properties. For environmental barrier coatings, the most studied are rare earth silicate materials. CMAS reacts with them at high temperatures to form garnet, apatite, quartz, etc., and the melt infiltrates along the grain boundaries, causing cracks and peeling of the EBC, and losing its protective function for CMC. Summary of the invention
[0005] In response to the problem of CMAS corrosion damaging TBC and EBC, the present invention proposes a simple and low-cost protection method, that is, to construct a CMAS corrosion-resistant protective layer with a bionic structure on the surface of the coating through an in-situ chemical reaction. The top layer of the protective layer is composed of vertically grown needle-shaped apatite, which gives the protective layer the function of repelling molten CMAS, and the bottom layer is a continuous dense layer, which effectively prevents the infiltration of molten CMAS. Under engine operating conditions, it will be difficult for molten CMAS to adhere to the surface of TBC and EBC with such a bionic structure protective layer, and even if there is a small amount of adhesion, it is difficult for the melt to penetrate into the coating. This bionic structure protective layer has good high-temperature stability, good compatibility with thermal barrier / environmental barrier coatings, excellent CMAS corrosion resistance, and is suitable for use in aircraft engines and gas turbines.
[0006] The present invention provides a CMAS corrosion resistant protective layer for thermal barrier coating and environmental barrier coating of aircraft engine / gas turbine. The protective layer has a bionic structure and is formed by in-situ chemical reaction on the surface of thermal barrier coating and environmental barrier coating. The thickness is 10-30 μm, and the top layer is composed of vertically grown needle-shaped apatite, denoted as T 1 ; The bottom layer is a continuous dense layer, denoted as T 2 , the thickness ratio of the two is T 1 / T 2 =1-3. The CMAS corrosion protection layer preparation method is simple, the process is flexible and the cost is low, and it can be prepared at any designated position of the thermal barrier coating and environmental barrier coating workpiece. The protective layer has good high temperature stability and good matching with the thermal barrier / environmental barrier coating. The molten CMAS has low wettability and is difficult to penetrate on its surface, which is suitable for providing CMAS protection for thermal barrier coatings and environmental barrier coatings of aircraft engines / gas turbines.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] Thermal barrier / environmental barrier coating anti-CMAS corrosion protection layer; construct an anti-CMAS corrosion protection layer with a bionic structure on the surface of the coating, the top layer of the protection layer is composed of vertically grown needle-shaped apatite, denoted as T 1 ; The bottom layer is a continuous dense layer, denoted as T 2 ; The thickness ratio of the two is T 1 / T 2 =1~3.
[0009] The method for preparing the CMAS corrosion resistant protective layer of the thermal barrier / environmental barrier coating of the present invention comprises the following steps:
[0010] 1) Preparation on the surface of thermal barrier coating or environmental barrier coating (Gd 1-x Yb x )PO 4 Layer, x = 0~1;
[0011] 2) CaO, MgO, SiO 2 (CMS) powders are uniformly mixed, the mixed powders are heat treated at high temperature to be in a molten state, then taken out and poured into deionized water, and ground to obtain CMS amorphous powder; in (Gd 1-x Yb x )PO 4 The surface of the layer is pre-coated with CMS amorphous powder;
[0012] 3) will carry (Gd 1-x Yb x )PO 4The thermal barrier coating or environmental barrier coating sample / workpiece pre-coated with CMS amorphous powder is placed in a high-temperature furnace for heat treatment, and an anti-CMAS corrosion protection layer with a bionic structure is formed by in-situ chemical reaction.
[0013] The CaO, SiO 2 The mass percentage of MgO powder is CaO: 25-35wt%; SiO 2 : 45~55wt%; the balance is MgO.
[0014] In the step 1), (Gd 1-x Yb x )PO 4 The layer thickness is 5-20 μm.
[0015] The step 1) prepares (Gd 1-x Yb x )PO 4 The layer is prepared on the surface of the ceramic thermal insulation layer or the environmental barrier layer by atmospheric plasma, electron beam physical vapor deposition, plasma spraying-physical vapor deposition or slurry method.
[0016] In the step 2), the concentration of the pre-coated CMS amorphous powder is 5-15 mg / cm 2 .
[0017] In the step 3), the heat treatment temperature is 900-1250° C. and the time is 0.5-4 h.
[0018] In the step 3), the thickness of the in-situ generated anti-CMAS corrosion protection layer with a bionic structure is 10 to 30 μm.
[0019] The anti-CMAS protective layer with bionic structure described in the present invention can effectively improve the adaptability of hot end components of aircraft engines and gas turbines in harsh high temperature and corrosive environments. 2 The CMAS powder was subjected to CMAS corrosion test at 1250℃. The CMAS powder on the sample surface was completely melted, but it did not spread evenly on the sample surface, but gathered into droplets, just like water drops falling on lotus leaves. The sessile drop method was used to characterize the contact angle of molten CMAS on the surface of the bionic structure, which significantly improved the contact angle of molten CMAS on the surface of the thermal barrier / environmental barrier coating.
[0020] The bottom of the invented anti-CMAS corrosion protective layer is continuous and dense, which can prevent molten CMAS from infiltrating the thermal barrier coating and the environmental barrier coating; the top layer is composed of vertically growing needle-shaped apatite, presenting a lotus leaf-like bionic structure, which can greatly reduce the wettability of molten CMAS on the surface of the protective layer. Then, under the high-speed rotation of the engine blades and the action of high-speed airflow, it will be extremely difficult for molten CMAS to adhere to the blade surface, thereby reducing the corrosion of the thermal barrier coating and the environmental barrier coating at the root.
[0021] The invention discloses a method for preparing the CMAS corrosion resistant protective layer, which is simple and flexible in process. 1-x Yb x )PO 4 (x=0~1) layer and CMS amorphous powder, and then undergo high-temperature treatment, and in-situ reaction to form an anti-CMAS corrosion protective layer. This method is basically not limited by the complex shape of the engine blade, and the protective layer can be generated in-situ at any specified position of the blade, with flexible design, easy operation and low cost.
[0022] The invented anti-CMAS corrosion protection layer has an equilibrium contact angle with molten CMAS at 1250°C increased by 20-40°. In addition, the formed protection layer has good high-temperature stability and good compatibility with thermal barrier / environmental barrier coatings. After heat treatment at 1100-1300°C for 30-50h, the protection layer of this bionic structure still maintains its original structure and has good high-temperature stability. After 65 water quenching thermal cycle tests at 1050°C, the area of the bionic structure protection layer peeling off is less than 10%, and it has good compatibility with the thermal barrier coating below. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the structure of the thermal barrier coating's anti-CMAS corrosion protection layer;
[0024] Figure 2 This is a schematic diagram of the structure of the environmental barrier coating's anti-CMAS corrosion protection layer;
[0025] Figure 3 The cross-sectional microstructure of the CMAS corrosion protection layer with a bionic structure;
[0026] Figure 4 Surface morphology of molten CMAS on a thermal barrier coating sample with a bionic structure anti-CMAS corrosion protection layer. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the present invention clearer and more specific, the present invention is further described below through specific embodiments.
[0028] The present invention provides a CMAS corrosion resistant protective layer and a preparation method thereof for aero-engine / gas turbine thermal barrier coating and environmental barrier coating. Figure 1 and Figure 2 is a schematic diagram of the protective layer, which has a thickness of 10 to 30 μm and a bionic structure, and the top layer is composed of vertically growing needle-shaped apatite, denoted as T 1 ; The bottom layer is a continuous dense layer, denoted as T 2 , the thickness ratio of the two is T 1 / T 2 =1-3. The preparation of the protective layer comprises the following specific steps:
[0029] 1) Prepare the ceramic insulation layer of thermal barrier coating or the surface layer of environmental barrier coating by atmospheric plasma, electron beam physical vapor deposition, plasma spray-physical vapor deposition or slurry method (Gd 1-x Yb x )PO 4 (x=0~1) layer, thickness is 5-20μm;
[0030] 2) In (Gd 1-x Yb x )PO 4 The surface of the layer is pre-coated with CMS amorphous powder, with a powder concentration of 5-15 mg / cm 2 ;
[0031] 3) Place the sample in a high temperature furnace for heat treatment at a temperature of 900-1250°C for 0.5-4h. 1- x Yb x )PO 4 Through in-situ chemical reaction with CMS amorphous powder, an anti-CMAS corrosion protection layer with a bionic structure is formed.
[0032] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0033] Example 1
[0034] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of a thermal barrier coating of an aero-engine, is prepared by the following steps:
[0035] 7wt% Y prepared by atmospheric plasma spraying method 2 O 3 Partially stabilized ZrO 2 (YSZ) ceramic layer;
[0036] 1) GdPO with a thickness of about 5 μm was prepared by atmospheric plasma spraying 4 layer;
[0037] 2) In GdPO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 5 mg / cm2 ; The specific composition is: CaO: 25wt%, SiO 2 : 55wt%, MgO: 20wt%;
[0038] 3) The sample was placed in a high temperature furnace for heat treatment at 1250°C for 1 h. 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically grown needle-shaped apatite.
[0039] Figure 3 The cross-sectional microstructure of the prepared anti-CMAS corrosion protection layer with bionic structure. The bottom layer of the protection layer is continuous and dense, with a thickness of about 4 to 6 μm, and the top layer is composed of vertically grown needle-shaped apatite, with a thickness of about 10 to 13 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with bionic anti-CMAS corrosion protection layer. After heat treatment at 1250℃ for 0.5h, the macroscopic morphology of the sample is as follows: Figure 4 As shown. The CMAS powder on the surface of the sample is completely melted, but it is not evenly spread on the surface of the sample, but gathers into droplets, just like water drops falling on a lotus leaf. Therefore, the thermal barrier coating with a bionic structure anti-CMAS corrosion protective layer exhibits excellent molten CMAS characteristics, mainly due to the vertical growth of needle-like apatite on the top layer of the protective layer, which gives the original coating a microstructure similar to a lotus leaf. The contact angle of the 7YSZ thermal barrier coating without a bionic structure protective layer with the molten CMAS at 1250°C is 9-12°; the contact angle of the 7YSZ thermal barrier coating with a bionic structure protective layer with CMAS is increased by about 30° to 37-44°. In addition, this bionic structure protective layer still maintains its original structure after heat treatment at 1100°C for 50h, and has good high temperature stability. After 65 water quenching thermal cycle tests at 1050°C, the area of the bionic structure protective layer peeling off is less than 10%, and it has good matching with the thermal barrier coating below.
[0040] Example 2
[0041] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of a thermal barrier coating of an aero-engine, is prepared by the following steps:
[0042] Prepare Gd by electron beam physical vapor deposition 2 Zr 2 O 7 Ceramic layer;
[0043] 1) Prepare 20 μm (Gd 0.25 Yb 0.75 )PO 4 layer;
[0044] 2) In (Gd0.25 Yb 0.75 )PO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 15 mg / cm 2 ; The specific composition is: CaO: 27wt%, SiO 2 : 41wt%, MgO: 32wt%;
[0045] 3) The sample was placed in a high temperature furnace for heat treatment at 1100°C for 3 h. 0.25 Yb 0.75 )PO 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically growing needle-shaped apatite.
[0046] The prepared anti-CMAS corrosion protection layer with bionic structure has a continuous and dense bottom layer with a thickness of about 8 to 10 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 17 to 20 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with a bionic structure anti-CMAS corrosion protection layer. After heat treatment at 1250°C for 2 hours, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water droplets falling on a lotus leaf, and there was no CMAS infiltration into the thermal barrier coating. Therefore, the thermal barrier coating with a bionic structure anti-CMAS corrosion protection layer exhibits excellent anti-CMAS corrosion performance. Gd without a bionic structure protection layer 2 Zr 2 O 7 The contact angle of the thermal barrier coating with molten CMAS at 1250°C is 19-21°; the Gd with bionic structure protective layer 2 Zr 2 O 7 The contact angle between the thermal barrier coating and CMAS increased by about 20° to 38-42°. In addition, the protective layer of this bionic structure has good high-temperature stability and good matching with the thermal barrier coating below. After heat treatment at 1300°C for 50 hours, the protective layer of this bionic structure still maintains its original structure and has good high-temperature stability. After 65 water quenching thermal cycle tests at 1050°C, the area of peeling of the protective layer of the bionic structure is less than 10%, and it has good matching with the thermal barrier coating below.
[0047] Example 3
[0048] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of a gas turbine thermal barrier coating, is prepared by the following steps:
[0049] 8wt% Y prepared by electron beam physical vapor deposition method 2 O 3Partially stabilized ZrO 2 (YSZ) ceramic layer;
[0050] 1) Prepare about 12μm (Gd 0.75 Yb 0.25 )PO 4 layer;
[0051] 2) In (Gd 0.75 Yb 0.25 )PO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 8 mg / cm 2 ; The specific composition is: CaO: 30wt%, SiO 2 : 50wt%, MgO: 20wt%;
[0052] 3) The sample was placed in a high temperature furnace for heat treatment at 940°C for 4 h. 0.75 Yb 0.25 )PO 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically grown needle-shaped apatite.
[0053] The prepared anti-CMAS corrosion protective layer with bionic structure has a continuous and dense bottom layer with a thickness of about 6 to 9 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 13 to 15 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with bionic structure anti-CMAS corrosion protective layer. After heat treatment at 1250℃ for 1h, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water drops falling on lotus leaves, and there was no CMAS infiltration into the thermal barrier coating. Therefore, the thermal barrier coating with bionic structure anti-CMAS corrosion protective layer exhibits excellent anti-CMAS corrosion performance. The contact angle of molten CMAS at 1250℃ on the surface of the thermal barrier coating with bionic structure protective layer increased by 20 to 24°. In addition, this bionic structure protective layer has good high temperature stability and good matching with the thermal barrier coating below.
[0054] Example 4
[0055] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of a gas turbine thermal barrier coating, is prepared by the following steps:
[0056] Prepare Gd by plasma spray-physical vapor deposition method 2 O 3 , Yb 2 O 3 Doped ZrO 2 (GYbZ) ceramic layer;
[0057] 1) Preparation of 18 μm GdPO by equal slurry method 4 layer;
[0058] 2) In GdPO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 15 mg / cm 2 ; The specific composition is: CaO: 35wt%, SiO 2 : 45wt%, MgO: 20wt%;
[0059] 3) The sample was placed in a high temperature furnace for heat treatment at 900°C for 4 h. 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically growing needle-shaped apatite.
[0060] The prepared anti-CMAS corrosion protective layer with bionic structure has a continuous and dense bottom layer with a thickness of about 7 to 12 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 18 to 21 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with bionic structure anti-CMAS corrosion protective layer. After heat treatment at 1220℃ for 1h, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water drops falling on lotus leaves, and there was no CMAS infiltration into the thermal barrier coating. Therefore, the thermal barrier coating with bionic structure anti-CMAS corrosion protective layer exhibits excellent anti-CMAS corrosion performance. The contact angle of molten CMAS at 1250℃ on the surface of the thermal barrier coating with bionic structure protective layer increased by 27 to 32°. In addition, this bionic structure protective layer has good high temperature stability and good matching with the thermal barrier coating below.
[0061] Example 5
[0062] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of an aero-engine environmental barrier coating, is prepared by the following steps:
[0063] Yb prepared by plasma spray-physical vapor deposition method 2 Si 2 O 7 Environmental barrier layer;
[0064] 1) Plasma spray-physical vapor deposition method was used to prepare (Gd 0.5 Yb 0.5 )PO 4 layer;
[0065] 2) In (Gd 0.5 Yb0.5 )PO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 9 mg / cm 2 ; The specific composition is: CaO: 30wt%, SiO 2 : 45wt%, MgO: 25wt%.
[0066] 3) The sample was placed in a high temperature furnace for heat treatment at 1200°C for 3 h. 0.5 Yb 0.5 )PO 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically growing needle-shaped apatite.
[0067] The prepared anti-CMAS corrosion protective layer with bionic structure has a continuous and dense bottom layer with a thickness of about 5 to 7 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 13 to 16 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with bionic structure anti-CMAS corrosion protective layer. After heat treatment at 1350℃ for 2h, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water droplets falling on lotus leaves, and there was no CMAS infiltration into the environmental barrier coating. Therefore, the environmental barrier coating with bionic structure anti-CMAS corrosion protective layer exhibits excellent anti-CMAS corrosion performance. The contact angle of molten CMAS at 1250℃ on the surface of the thermal barrier coating with bionic structure protective layer increased by 21 to 25°. In addition, this bionic structure protective layer has good high temperature stability and good matching with the thermal barrier coating below.
[0068] Example 6
[0069] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of an aero-engine environmental barrier coating, is prepared by the following steps:
[0070] Ready to use electron beam physical vapor deposition to produce Y 2 SiO 5 Environmental barrier layer;
[0071] 1) 5 μm YbPO was prepared by electron beam physical vapor deposition 4 layer;
[0072] 2) In YbPO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 5 mg / cm 2 ; The specific composition is: CaO: 25wt%, SiO 2 : 45wt%, MgO: 30wt%;
[0073] 3) The sample was placed in a high temperature furnace for heat treatment at 1250°C for 0.5 h. 4 The layer undergoes an in-situ chemical reaction with the CMS amorphous powder to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically growing needle-shaped apatite.
[0074] The prepared anti-CMAS corrosion protective layer with bionic structure has a continuous and dense bottom layer with a thickness of about 4 to 7 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 7 to 12 μm. CMAS powder was coated on the surface of the environmental barrier coating sample with bionic structure anti-CMAS corrosion protective layer. After heat treatment at 1350℃ for 2h, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water droplets falling on lotus leaves, and there was no CMAS infiltration into the environmental barrier coating. Therefore, the environmental barrier coating with bionic structure anti-CMAS corrosion protective layer exhibits excellent anti-CMAS corrosion performance. The contact angle of molten CMAS at 1250℃ on the surface of the thermal barrier coating with bionic structure protective layer increased by 25 to 30°. In addition, this bionic structure protective layer has good high temperature stability and good matching with the thermal barrier coating below.
[0075] Example 7
[0076] A CMAS corrosion protection layer with a bionic structure, used for CMAS corrosion protection of a thermal barrier coating of an aero-engine, is prepared by the following steps:
[0077] Prepare YTaO by plasma spray-physical vapor deposition method 4 Ceramic layer;
[0078] 1) Preparation of 14 μm (Gd 0.9 Yb 0.1 )PO 4 layer;
[0079] 2) In (Gd 0.9 Yb 0.1 )PO 4 The surface of the layer is coated with CMS amorphous powder with a powder concentration of 10 mg / cm 2 ; The specific composition is: CaO: 33wt%, SiO 2 : 48wt%, MgO: 19wt%;
[0080] 3) The sample was placed in a high temperature furnace for heat treatment at 1200°C for 3 h. 0.9 Yb 0.1 )PO 4The CMS amorphous powder undergoes an in-situ chemical reaction to form a bionic structural protective layer with a continuous and dense bottom layer and a top layer composed of vertically growing needle-shaped apatite.
[0081] The prepared anti-CMAS corrosion protective layer with bionic structure has a continuous and dense bottom layer with a thickness of about 6 to 10 μm, and a top layer composed of vertically grown needle-shaped apatite with a thickness of about 12 to 15 μm. CMAS powder was coated on the surface of the thermal barrier coating sample with bionic structure anti-CMAS corrosion protective layer. After heat treatment at 1250℃ for 2h, the CMAS powder on the surface of the sample was completely melted, but it did not spread evenly on the surface of the sample, but gathered into droplets, like water droplets falling on lotus leaves, and there was no CMAS infiltration into the thermal barrier coating. Therefore, the thermal barrier coating with bionic structure anti-CMAS corrosion protective layer exhibits excellent anti-CMAS corrosion performance. The contact angle of molten CMAS at 1250℃ on the surface of the thermal barrier coating with bionic structure protective layer increased by 35 to 40°. In addition, this bionic structure protective layer has good high temperature stability and good matching with the thermal barrier coating below.
[0082] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A method for preparing a CMAS corrosion protection layer of a thermal barrier / environmental barrier coating, characterized in that: The steps include: Preparation of thermal barrier coatings or environmental barrier coatings (Gd 1-x Yb x )PO4 layer, x=0~1; The CaO, MgO, and SiO2 (CMS) powders are uniformly mixed, and the mixed powders are heat treated at high temperature to be in a molten state, and then taken out and poured into deionized water, and CMS amorphous powder is obtained after grinding; in (Gd 1-x Yb x ) The surface of the PO4 layer is pre-coated with CMS amorphous powder; Will have (Gd 1-x Yb x )PO4 layer, thermal barrier coating or environmental barrier coating sample / workpiece pre-coated with CMS amorphous powder is placed in a high-temperature furnace for heat treatment, and an anti-CMAS corrosion protection layer with a bionic structure is formed by in-situ chemical reaction.
2. The method according to claim 1, characterized in that: The mass percentages of CaO, SiO2 and MgO powders are as follows: CaO: 25~35wt%; SiO2: 45~55wt%; and the balance is MgO.
3. The method according to claim 1, characterized in that: In step 1), (Gd 1-x Yb x )The thickness of the PO4 layer is 5-20μm.
4. The method according to claim 1, characterized in that: In step 2), the concentration of the pre-coated CMS amorphous powder is 5-15 mg / cm 2 .
5. The method according to claim 1, characterized in that: In step 3), the heat treatment temperature is 900-1250° C. and the time is 0.5-4 h.
6. The method according to claim 1, characterized in that the step 1) Preparation (Gd 1-x Yb x )PO4 layer is prepared on the surface of ceramic thermal insulation layer or environmental barrier layer by atmospheric plasma, electron beam physical vapor deposition, plasma spraying-physical vapor deposition or slurry method.
7. The thermal barrier / environmental barrier coating anti-CMAS corrosion protection layer prepared by the method according to any one of claims 1 to 6, characterized in that: An anti-CMAS corrosion protective layer with a bionic structure is constructed on the surface of the coating. The top layer of the protective layer is composed of vertically grown needle-shaped apatite with a thickness of T1; the bottom layer is a continuous dense layer with a thickness of T2; the thickness ratio of the two is T1 / T2=1~3.
Citation Information
Patent Citations
CMAS bonding-resistant bionic thermal barrier coating and preparation method thereof
CN114457307A
